KEPATUHAN WAJIB PAJAK BADAN INDUSTRI GARMEN DI SEMARANG DALAM PERSPEKTIF TAX PROFESSIONAL - Dhisa Deviana, 11.05.52.0006; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2015)
In order to increase revenues in todays world where competition in the form of business intensifies, the government needs to do some efforts and policies in the field of taxation. One cause is not optimal tax revenues in Indonesia caused by the level of tax compliance and private entities in paying taxes is still very low. The diversity profile of someone from differences in gender, age, and education level, then weak and pemahamaan knowledge, the financial condition of the company, the companys environmental, behavioral control and subjective norms someone who causes the taxpayer compliance rate in Indonesia is still low in addition to lack of awareness of the taxpayer in paying taxes. Sample in this study was chosen by 73 respondents by using purposive sampling and convenience on tax professionals who work in the garment industry in the city of Semarang. Data obtained by distributing questionnaires. Data analysis was performed using multiple linear regression analysis with SPSS 16.00. The results of this study indicate that knowledge and understanding of tax laws are not significant negative effect on tax compliance agencies, financial condition was not significant positive effect on tax compliance agencies, corporate environment is not significant positive effect on compliance with corporate taxpayers, control the behavior of a significant positive effect on tax compliance body, and subjective norm significant negative effect on tax compliance body.Keywords: Compliance With Corporate Taxpayers, Knowledge and Understanding of Tax Laws, The Financial Condition of The Company, The Company Environment, Behavioral Control and Subjective Norms